You would move all terms that don’t contain x to the right side and solve. Answer : x= -3
Answer: g(4)= -60
Step-by-step explanation:
You just plug in 4 into the equation
g(4)= 2√4 - (4)³
g(4)= 2√4 - (4)³
g(4)= 2·2 - (64)
g(4)= 4 - 64
g(4)= -60
Answer:
17
Step-by-step explanation:
I must assume that you meant the following:
10(Q-3R)
P = ----------------
R
Multiplying both sides by R, we get PR = 10R(Q-3R), or PR = 10RQ - 30R^2.
Rearranging these terms so that powers of R are in descending order:
30R^2 - 10RQ + PR = 0
Factoring out R, we get
R(30R - 10Q + P) = 0. This has two solutions:
R = 0, and 10Q - P
30R = 10Q - P, so that R = --------------
30